Thermally Radiation of MHD Two-Phase Williamson Fluid with Newtonian Heating (NH) - S.M.H, Mohd Kanafiah; Abdul Rahman, Mohd Kasim; N. S., Arifin; S., Shafie; Noor Amalina Nisa, Ariffin (Akademi Sains Malaysia, 2023)
Due to the unique qualities in its behaviours that study the solid and fluid aspects, a study on twophase flow (solid and liquid) is deemed to be supplementary trustworthy in describing the application of liquid in industrial sectors. Over the past few decades, several non-Newtonian fluid models have been found, but the Williamson model stands out as the most intriguing. The Williamson flow model will be more fascinating to study when the existing particles are considered. Therefore, the purpose of this article is to investigate Williamson fluid with dust particles under the existing MHD and heat radiation. To make inquiry more intriguing, the analysed model also included a Newtonian heating (NH) condition. After employing similarity transformation, the resultant equations, as in Ordinary Differential Equations (ODEs), are solved using the Runge-Kutta Fehlberg (RKF45) method. The findings showed that the presence of fluid-particle interaction (FPI) influenced the fluid velocity, subsequent in a declining the fluid movement and an increase in particle motion